The Use of Picture Media to Improve Indonesian Class III Learning Outcomes SDN 114345 Gunung Melayu, North Labuhan Batu Regency, Academic Year 2023/2024 - Darling Krisman Zega; Melinna Harefa; Reni Violina Simanjuntak; Rini Agustina; Ulina Rahmayani (Formosa Journal of Science and Technology, 2023)
This study aims to improve learning outcomes in Indonesian by using media images as learning media for third grade students at SD Negeri 114345 Gunung Melayu. This study uses several theories and definitions as a theoretical approach. Among them are the notion of use, the notion of image media, the notion of improving, and the notion of learning outcomes. The action hypothesis in this study is that by using image media as a learning medium, it can improve student learning outcomes in the Indonesian subject reading learning material for class III SDN 114345 Gunung Malay Labuhan Batu Utara Regency for the 2023/2024 Academic Year. This research was conducted at SDN 114345 Gunung Melayu, North Labuhan Batu District, 2023/2024 Academic Year. The subjects in this study were 10 students in class III SD Negeri 114345 Gunung Melayu and the object of this study was to improve learning outcomes in Indonesian with media images. The results of the tests carried out in cycle I contained 3 students who had completed their studies and 7 students who had not completed their studies with an average score of 56.5. The frequency value that often appears is 65-80. In cycle II, the number of students who have completed their studies is 8 students who have completed and only 2 students (8.11%) have not completed with an average score of 72.5. The frequency of values ​​that often appear has increased to 65-90. Thus there is an increase in student completeness 40.65 from cycle I.